(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article discusses the life path of the great scholar Alisher Navoi, his contributions to the establishment of unique architectural monuments in Herat and other cities of the country at his own expense, as well as his scientific and journalistic works, historical and religious treatises. It emphasizes his lifelong dedication to wisdom, nobility, and service to the people, as well as the exceptional example of enlightenment he set. The article also explores the themes of justice, truthfulness, generosity, and nobility in his poetry, along with ethical, philosophical, and socio-political issues reflected in his creative works.